4 Wurzeln in der Naturheilkunde - Stern, Cornelia; Stapelfeldt, Elmar; Stern, Cornelia; Ptok, Agnes (Deutsche Heilpraktiker-Zeitschrift, 2024)
4 Expert*innen stellen Ihnen 4 Wurzeln in verschiedenen Heiltraditionen vor.
Keywords: 4 Fachleute; Narde; Kurkuma; Galgant; Baldrian